2021
DOI: 10.1007/s11606-021-07010-1
|View full text |Cite
|
Sign up to set email alerts
|

The State of Morning Report in the Current Healthcare Landscape: a National Survey of Internal Medicine Program Directors

Abstract: Background Case-based Morning Report (MR) has long been the predominant educational conference in Internal Medicine (IM) residency programs. The last comprehensive survey of IM MR was in 1986. Much has changed in the healthcare landscape since 1986 that may impact MR. Objective We sought to determine the current state of MR across all US IM programs. Design In 2018, US IM program directors (PDs) were surveyed about the dynamics of MR at their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…A recent national survey of internal medicine program directors reported that the most common goals of morning report were to develop clinical reasoning and resident knowledge acquisition 5 . Our results suggest that scripted and unscripted formats have complementary strengths.…”
Section: Discussionmentioning
confidence: 63%
“…A recent national survey of internal medicine program directors reported that the most common goals of morning report were to develop clinical reasoning and resident knowledge acquisition 5 . Our results suggest that scripted and unscripted formats have complementary strengths.…”
Section: Discussionmentioning
confidence: 63%
“…This may in turn alter approaches to case-based presentations to reflect the learning priorities and teaching methods preferred by residents 7,15 . Our results indicate an important change in the number of slides used to present content in the virtual setting, which may affect case sequencing and opportunities for clinical reasoning and problem solving valued by program leaders in this setting 22 …”
Section: Discussionmentioning
confidence: 89%
“…7,15 Our results indicate an important change in the number of slides used to present content in the virtual setting, which may affect case sequencing and opportunities for clinical reasoning and problem solving valued by program leaders in this setting. 22 Morning report extends beyond clinical teaching, prioritizing connections between faculty and learners, and is a forum for dialog about experiences in specific clinical settings. Although care delivery pressures have decreased its frequency and duration, 22 morning report continues to be a cornerstone of academic internal medicine, prioritizing exchanges between trainees and faculty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational and administrative duties remain core features of the position ( 4 ). CRs continue to facilitate conferences such as Morning Report and are increasingly involved in other educational activities such as simulation teaching ( 5 ). Similarly, administrative duties such as resident scheduling and food delivery remain common.…”
Section: Discussionmentioning
confidence: 99%